Distribution of grain size and organic elemental composition of the surficial sediments in Lingding Bay in the Pearl River Delta, China: A record of recent human activity. (1st August 2019) - Yuan, Xiuquan; Yang, Qingshu; Luo, Xiangxin; Yu, Fengling; Liu, Feng; Li, Jiayi; Wang, Zhanghua
Abstract: The Pearl River Delta (PRD) in China is severely affected by intensive human activities. In this study, we used surficial sediments collected in its Lingding Bay (LDB) in December 2016 to analyse the grain size and organic carbon composition and to identify the recent human impact recorded in the sediments. We examined the temporal variations in the spatial distribution of the grain size and organic elemental geochemistry of the surficial sediments by comparison with previous studies. Our study shows that in 2016, there were several patches of coarse-grained sediments, which were not consistent with the hydrodynamic conditions in LDB. Compared with the organic carbon composition in 2005–2006, the δ 13 C values in 2016 were more negative and the contribution of terrigenous organic matter (TOM) to the surficial sediments was significantly greater. There were also several patches of high TOM values in the outer LDB. The overall coarser sediments and lighter δ 13 C of organic carbon were in contrast to the decline in the riverine sediment supply and the increased eutrophication in recent decades. Furthermore, the anomalous patches of coarse-grained sediments and terrestrially sourced organic carbon were mainly distributed in the navigation channels and on their adjacent shoals, reflecting channel dredging, dumping, and sand mining activities. Therefore, the origins and spatial distributions of the grain size and organic carbon composition of the surficial sediments in LDB in 2016 were not controlled by hydrodynamic conditions and land–sea interactions, but overwhelmingly by human activities. We suggest that LDB of PRD exemplifies an anthropogenically controlled bay. Highlights: Irregular patches of coarse-grained surficial sediments in the LDB in 2016. An overall heavier δ 13 C and increased TOM in the surficial sediments. Human activities have overwhelmed the sediment dynamic processes in the LDB.